Simultaneous Determination of Migration Amounts of 14 Kinds of Bisphenol Substances in Food Metal Cans and Effect of Sterilization on the Migration - Yuling ZHANG; Gang WU; Hongbo GAO; Xun QIU; Xiaoming YANG; Qianqian ZHAO; Tongtong XU; Ya WANG (Shipin gongye ke-ji, 2022)
In order to investigate the migration amounts of bisphenol substances (BPs) in domestic food metal cans, a method of simultaneous detection of 14 kinds of BPs in food metal cans with high sensitivity was established by high performance liquid chromatography (HPLC). The effect of sterilization process on the migration of BPs and the migration laws of BPs in food metal cans were studied. Results showed that, all the 14 kinds of BPs were well separated and exhibited excellent linear characteristics in four kinds of food simulants (4 vol% acetic acid, 10 vol% ethanol, 50 vol% ethanol and isooctane). The precision and accuracy of the method was excellent with the recovery of the 14 kinds of BPs from 83.67%～107.05% and the relative standard deviations (RSDs) from 2.32%～7.67%, indicating that HPLC method was effective for simultaneous determination of 14 kinds of BPs in food metal cans. The amounts of 14 kinds of BPs migrated from nine kinds of canned foods and beverages on the Chinese market were simultaneously determined, and found seven kinds of BPs were detected while no BPA and its analogues were detected in all samples. BADGE·H2O migrating from the luncheon meat can, BADGE·2H2O migrating from the oyster pueraria beverage can and BFDGE·2H2O migrating from the blackberry all had the risk according to EU regulation. In addition, the sterilization process affected the amounts and types of BPs migrating from the food metal cans. After migration tests, only BADGE·2H2O was detected in sterilized cans while both BADGE·2H2O and BADGE·H2O·HCl were detected in unsterilized cans. Moreover, the type of food simulants also affected the amount and types of BPs migrating from food metal cans. With the increasing of migration temperature or time, the migration amounts of BPs increased at first and finally kept steady when the migration reached equilibrium.